Influência do sistema adrenérgico na enzima Na+, K+- ATPase no aparecimento de fadiga em córtex de ratos - Bertomeu, Judit Borras (2021)
Physical exercise brings health benefits, such as reducing neurological diseases and improving the immune system. Although exercise brings such benefits, it is also a stressor for the body, and may impact the immune and inflammatory response through two main neural pathways: the hypothalamus – pituitary – adrenal (HPA) axis; and the sympathetic nervous system (SNS). The adrenergic pathway plays an important role in physical performance and may influence, during physical activity, the work of important enzymes such as Na+,K+ -ATPase (NKA). However, information on how the adrenergic system acts on the central nervous system (CNS) during the onset of fatigue is lack. This study aims to investigate the involvement of the adrenergic pathway in the CNS during the onset of fatigue and what would be the relationship with the activity of NKA, a key enzyme in maintaining cell function. Male Wistar rats were divided into 3 groups (sedentary group, one-set swimming group and three-set swimming group) submitted to an exhaustive swimming exercise, with a load of 13% of body weight. In addition, strength analysis and motor patterns were performed during the three sets. The cortex was analyzed using Western Blot techniques and NKA activity, in addition to an in-vitro treatment with different concentrations of Noradrenaline. The results showed that three sets of exhaustive swimming did not cause an adaptation in swimming time. Strength gains were obtained in the three-swimming set (P=0.0022). NKA activity was shown to be increased after 3 sets (P=0.0032). The concentrations of 1μM (P=0.0005) and 10μM (P=0.0179) of norepinephrine also increased NKA enzyme activity. A single set of swimming increased the levels of 4HNE (P=0.0027) product of lipid peroxidation followed by a decrease after 3 sets of swimming in total antioxidant capacity (P=0.0011). These results demonstrate that the exhaustion process caused by the three swimming sets is located in the central nervous system. The increase in NKA activity demonstrated that 3 sets of swimming with NA treatment in slices of cortex could be affecting the α2-3 subunits of NKA. However, more studies need to be done to understand by which mechanism it would be modulated. We conclude that the exhaustive swimming protocol altered NKA activity in addition to a possible modulation through the adrenergic pathway, requiring further studies to confirm these findings.